Limits and opportunities to community health worker empowerment: A multi-country comparative study - Kane, Sumit; Kok, Maryse; Ormel, Hermen; Otiso, Lilian; Sidat, Mohsin; Namakhoma, Ireen; Nasir, Sudirman; Gemechu, Daniel; Rashid, Sabina; Taegtmeyer, Miriam; Theobald, Sally; de Koning, Korrie (Social science & medicine (1982), 2016)
In LMICs, Community Health Workers (CHW) increasingly play health promotion related roles involving ‘Empowerment of communities’. To be able to empower the communities they serve, we argue, it is essential that CHWs themselves be, and feel, empowered. We present here a critique of how diverse national CHW programs affect CHW's empowerment experience. We present an analysis of findings from a systematic review of literature on CHW programs in LMICs and 6 country case studies (Bangladesh, Ethiopia, Indonesia, Kenya, Malawi, Mozambique). Lee & Koh's analytical framework (4 dimensions of empowerment: meaningfulness, competence, self-determination and impact), is used. CHW programs empower CHWs by providing CHWs, access to privileged medical knowledge, linking CHWs to the formal health system, and providing them an opportunity to do meaningful and impactful work. However, these empowering influences are constantly frustrated by – the sense of lack/absence of control over one's work environment, and the feelings of being unsupported, unappreciated, and undervalued. CHWs expressed feelings of powerlessness, and frustrations about how organisational processual and relational arrangements hindered them from achieving the desired impact. While increasingly the onus is on CHWs and CHW programs to solve the problem of health access, attention should be given to the experiences of CHWs themselves. CHW programs need to move beyond an instrumentalist approach to CHWs, and take a developmental and empowerment perspective when engaging with CHWs. CHW programs should systematically identify disempowering organisational arrangements and take steps to remedy these. Doing so will not only improve CHW performance, it will pave the way for CHWs to meet their potential as agents of social change, beyond perhaps their role as health promoters. •Community health workers are a key bridge between communities and the health system.•For them to be able to empower communities, they must themselves be empowered.•Involvement with health services empowers community health workers in many ways.•However, many community health worker program aspects undermine this empowerment.•Community health workers need to be better supported by the health services.